Der Zweite Weltkrieg in postsozialistischen Gedenkmuseen: Geschichtspolitik zwischen der ,Anrufung Europas' und dem Fokus auf ,unser' Leid - Radonic, Ljiljana (2021)
Memorial museums are understood as flagships of the respective country's memory politics - in the context of transnational processes. How do big, publicly (co-)funded memorial museums that (re-)opened after 1989 in the eleven post-Communist EU member states exhibit the World War II period? Beyond a mere overview of the museum and their history the book analyzes how ,double' and ,tripple' occupation, Holocaust, victimhood and collaboration are represented in the permanent exhibitions and which role EU accession talks and authoritarian tendencies played and play in this.